Nephrotoxicity rates related to colistin and evaluation of risk factors - Asan, Ali; Karasu, Derya; Gül, Cuma Bülent; Akıncıoğlu, Gülsün; Koca, Nizameddin; Akça, Mustafa Özgür; Yılmaz, Canan; Karaduman, İsra and Köse, Şükran (The European Research Journal, 2020)
Objectives: Colistimethate sodium (colistin) is the member of polymyxins, the cyclic structured cationic polypeptide antibiotics. The purpose of our study is to determine the patients’ nephrotoxicity rates and risk factors related to nephrotoxicity development that are under colistin treatment in the tertiary intensive care unit (ICU). Methods: One-hundred colistin received patients files were reviewed retrospectively, who were in tertiary ICU in Bursa Yüksek Ihtisas Training and Research Hospital. Fifteen patients with the history of renal failurewere excluded from the study. The data before the first colistin treatment was taken into consideration for the patients received repetitive colistin treatment. RIFLE (Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease) classification was used for the evaluation of nephrotoxicity. Results: The patients mean age was 67.81 ± 16.56 years (range: 21-94) and 52.9% were male. Nephrotoxicity was determined in 35 (41.2%) patients. According to the RIFLE classification the nephrotoxicity rates were determined for risk, injury and deficiency were 24.7%, 10.6% and 5.9%, respectively. Nephrotoxicity was detectedin 9 (25.7%) out of 35 patients on the first day of the colistin treatment. Mortality rate was observed as 82.9% in patients with nephrotoxicity. Conclusions: Colistin treatment is preferable for the treatment of multi drug resistant infections in intensive care unit. The patients,under certain circumstances, i.e., malignancy, using additional nephrotoxic agent and elder age must be closely monitored for the possible nephrotoxicity development.